Refugee women's establishment in the rural north of Sweden: cultural capital in meeting local labour market needs. Issue 5 (4th April 2022) - Carlbaum, Sara
ABSTRACT : This paper investigates opportunities and obstacles refugee women face in establishment in rural areas. Drawing on ethnographic research in three rural municipalities in northern Sweden, including interviews with refugee women, local employers and educational staff, I analyse the women's space for agency and opportunities to use and capitalise on different resources in relation to the local labour market and belonging. Applying Bourdieu's conceptualisation of cultural capital, as read by Skeggs, I show that the women can capitalise on embodied cultural capital of feminine and ethnic caregiving. However, due to lack of the 'right' institutional cultural capital of educational certificates from Swedish institutions, and devaluation of foreign credentials and experiences, this is mainly in difficult-to-fill, unsecure jobs in the elder care or early childhood education and care sectors. The women's limited options and opportunities to 'enterprise themselves up' contribute to ethnicisation of care work in rural labour markets. Moreover, lack of mobility and key cultural capital (cars and driving licences) for work, education and belonging in both the local masculine culture of the remote rural areas and national gender equality culture further limit the women's space for agency and establishment.